2002
DOI: 10.1901/jeab.2002.77-147
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Against a Constant‐difference Effect in Concurrent‐chains Schedules

Abstract: Savastano and Fantino (1996) reported that in concurrent-chains schedules, initial-link choice proportions remained constant as terminal-link durations increased as long as the subtractive difference between the two terminal-link schedules remained constant. Two experiments with pigeons were conducted to examine this constant-difference effect. Both experiments used equal variable-interval schedules as initial links. The terminal links were fixed delays to reinforcement in Experiment 1 and variable delays to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…These delay values were used subsequently as the combinations of delays and magnitudes of reinforcement in the terminal links of a concurrent-chains procedure with equal variable-interval schedules in the initial links. It was expected that subjects would show roughly equivalent relative rates in the longer choice period of the free-operant procedure since it has been found that choice tends toward indifference with longer initial links (Fantino, 1969;Mazur, 2002;Wardlaw & Davison, 1974). However indifference estimates derived from the discrete-trials adjusting procedure tended to produce preference for the LLR when the reinforcement parameters were fixed in the procedure with longer initial links.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These delay values were used subsequently as the combinations of delays and magnitudes of reinforcement in the terminal links of a concurrent-chains procedure with equal variable-interval schedules in the initial links. It was expected that subjects would show roughly equivalent relative rates in the longer choice period of the free-operant procedure since it has been found that choice tends toward indifference with longer initial links (Fantino, 1969;Mazur, 2002;Wardlaw & Davison, 1974). However indifference estimates derived from the discrete-trials adjusting procedure tended to produce preference for the LLR when the reinforcement parameters were fixed in the procedure with longer initial links.…”
Section: Discussionmentioning
confidence: 99%
“…The choice period of these procedures is as brief as possible and so the actual delay between response and reinforcement is essentially the same as the scheduled delay. In free-operant procedures the length of the choice period serves as an additional delay that combines with the nominal delay (Mazur, 1987a), and such an additional delay contributes to determine the degree of preference for one alternative (Fantino, 1969;Mazur, 2002;Wardlaw & Davison, 1974).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the problem has not received as much research interest as have programs examining behavioral adaptation with increasing experience (Hull, 1943;Rescorla & Wagner, 1972), behavioral adaptation across an unsignaled temporal interval (Gallistel & Gibbon, 2000;Miller & Schachtman, 1985;Spence, 1956), or behavior to concurrently available alternatives (Baum, 1974;Herrnstein, 1970;Mazur, 2002). However, comprehensive principled models that can simultaneously accommodate acquisition, timing, choice, and within-trial events are essential if behavior is to be predicted in a wide variety of situations.…”
Section: Discussionmentioning
confidence: 99%
“…Questions about whether magnitudes should be scaled linearly or logarithmically may reflect the same fundamental indeterminacy (e.g., Dehaene, 2003;Dehaene, Izard, Spelke, & Pica, 2008;Gibbon & Church, 1981;Tan & Grace, 2012). Models for nonhuman choice behavior have also disagreed about whether differences or ratios of reinforcement-related variables control responding (Mazur, 2002;Savastano & Fantino, 1996).…”
mentioning
confidence: 99%